Technical and intellectual characteristics for existential theatre (Journal of the College of Basic Education, 2023)
Since its inception, the theater has been associated with philosophy, so the dramatic productions were a reflection of the prevailing philosophies in their various political, social, economic and ideological directions.In the twentieth century, there were a number of dramatic writers who did not adhere to any direction, but rather benefited from any technique that achieves the greatest possible amount of graphic expression for their goals. Examples of these we find in France in writers such as (Jean Giraudo), (Jean Cocteau) and (Jean-Paul Sartre). ) and in Switzerland (Frederic Dürrenmatt) and in America (Eugene O'Neill) and (Arthur Miller) and in Italy (Luigi Pera Ndello).